2024
DOI: 10.1126/science.adh0755
|View full text |Cite
|
Sign up to set email alerts
|

Defective pollen tube tip growth induces neo-polyploid infertility

Jens Westermann,
Thanvi Srikant,
Adrián Gonzalo
et al.

Abstract: Genome duplication (generating polyploids) is an engine of novelty in eukaryotic evolution and a promising crop improvement tool. Yet newly formed polyploids often have low fertility. Here we report that a severe fertility-compromising defect in pollen tube tip growth arises in new polyploids of Arabidopsis arenosa . Pollen tubes of newly polyploid A. arenosa grow slowly, have aberrant anatomy and disrupted physiology, often burst prematurely, and have altered ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…During the breeding process of NTR lines, OsNRFG6 had formed an improved genotype different from the parental lines (Yu et al 2020 ). Similar mechanism has been found that improved genotypes of fertility genes helped autotetraploid Arabidopsis arenosa to adjust its defective meiosis process and pollen tube tip growth (Morgan et al 2020 , 2021 ; Westermann et al 2024 ). Thus, the non-parental allele of OsNRFG6 may play important roles in the formation of high fertility of NTR lines.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…During the breeding process of NTR lines, OsNRFG6 had formed an improved genotype different from the parental lines (Yu et al 2020 ). Similar mechanism has been found that improved genotypes of fertility genes helped autotetraploid Arabidopsis arenosa to adjust its defective meiosis process and pollen tube tip growth (Morgan et al 2020 , 2021 ; Westermann et al 2024 ). Thus, the non-parental allele of OsNRFG6 may play important roles in the formation of high fertility of NTR lines.…”
Section: Discussionsupporting
confidence: 52%
“…The origin of regulation for high fertility of NTR or PMeS lines might relate to those improved genotypes of key genes formed during germplasm evolution (Koide et al 2020 ). For example, the evolved autotetraploid Arabidopsis arenosa (fertile) has formed alternate alleles of important fertility genes like ASY1 , ASY2 , ACA8 , and AGC1.5 to overcome its unstable meiotic chromosome axes, aberrant crossover interference, and defective pollen tube tip growth (Morgan et al 2020 , 2021 ; Westermann et al 2024 ). Similarly, 222–324 genes with different alleles between 13 fertile NTR lines and two sterile ATR parental lines (Jackson-4x and 96025-4x) were identified in genomic comparison (Bei et al 2019 ; Yu et al 2020 , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various factors affecting autotetraploidization sterility have been identified, including meiotic genes, miRNAs, long non-coding RNA, and DNA methylation sites [ 6 , 10 , 11 , 12 , 13 , 14 , 19 , 33 , 34 ]. Among these regulators, miRNAs with variable expression patterns have been proposed as an important factor for low fertility of autotetraploid rice.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of autopolyploidy and allopolyploidy, polyploid individuals have substantial advantages in stress resistance, biosynthesis, genomic buffering capacity, biodiversity, and heterosis [ 1 , 2 , 3 ]. However, the widespread complex reproductive defects in autotetraploid plants limit their application [ 4 , 5 , 6 , 7 ]. Autotetraploid rice, resulting from doubling its diploid counterpart, represents a promising breeding germplasm, which displays high salt and heavy metal ion resistance [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To stain callose, 0.1% aniline blue was added to cultured pollen tubes. To evaluate the distribution of demethylesterified pectin, pollen tubes were stained with 0.01% (w/v) ruthenium red for 5 min and washed in PGM 5 . To assess cell membrane integrity, 2.5 μg/ml CellMask ™ Plasma Membrane Stain (Invitrogen) was applied for 5 min followed by three washes in PGM.…”
Section: Methodsmentioning
confidence: 99%